The Itch-Scratch Cycle: A Review of the Mechanisms - Giulia Rinaldi (Mattioli1885, 2019)
Background: Despite being one of the most common presenting dermatological symptoms, itching continues to perplex health care professionals because it is notoriously difficult to control. Objective: This review gathers evidence to answer the 2-part question, "Why do we itch and scratch?" by exploring the history of itchy disease, the neurobiology of itch, and the 4 different clinical origins of itch: pruritogenic, neurological, neuropathic, and psychological. Results: The automated scratching reflex and its biological and psychological reasons for existence are complicated and poorly understood. Currently, there are a myriad of treatments available for individuals suffering from this condition; however, many remain symptomatic. Conclusions: The itch-scratch cycle is a complex pain-like sensation with a reflex-like response. In the future, continued exploration into the mechanisms behind itch and scratch may open the doors for new therapeutic interventions.